Preobrazba ljubezni v zreli in pozni ustvarjalnosti Franca Ksaverja Meška: med hrepenenjem, odpovedjo in predanostjo - Avsenik Nabergoj, Irena (Slavia Centralis, 2025)
The Transformation of Love in the Mature and Late Works of Franc Ksaver Meško: between Longing, Renunciation, and Devotion. The present paper offers a thematological and semiotic analysis of the transformation of love in the poetic, narrative, and drama works of Franc Ksaver Meško (1874–1964), presenting love as the emotional, ethical, and spiritual core of his poetics. Meško’s priestly vocation, which had led him to consciously renounce romantic love, profoundly shapes his literary imagination – from youthful idealization to renunciation, contemplation, and mystical devotion. Prominent motifs include romantic, maternal, patriotic, and saintly love, while his depictions of fallen women are imbued with empathy, inner conflict, and a didactic function. Meško’s writing draws on biblical patterns, Tolstoy’s The Power of Darkness, Cankar’s social sensitivity, and Andersen’s symbolism. This paper illuminates his portrayal of love as a symbolic language oscillating between longing and renunciation, emotional authenticity and transcendent silence, revealing the tension between the bodily and the spiritual, between silence and speech, and between suffering and sanctity.
Keywords: Franc Ksaver Meško; love as sacrifice; fallen maidens; intertextuality; priesthood and renunciation